Oxidative stability of tilapia feeds containing Saccharomyces cerevisiae and Spirulina platensis - Grassi, Thiago Luís Magnani [UNESP]; Sedlacek-Bassani, Juliana [UNESP]; Ponsano, Elisa Helena Giglio [UNESP] (FapUNIFESP (SciELO), 2020)
The aim of this study was to evaluate the effect of the inclusion of microbial biomass on the oxidative rancidity of tilapia rations stored for 12 months. Treatments included a control diet and diets supplemented with either 0.01% vitamin E, 0.25 and 0.5% of Saccharomyces cerevisiae and 0.25 and 0.5% of Spirulina platensis. Experimental diets were stored in the dark inside plastic bags at room temperature (25 °C) for 12 months. The oxidative rancidity was measured as thiobarbituric acid reactive substances (TBARS). It was concluded that the inclusions of Spirulina platensis at 0.25% (1.734 ± 0.206) and 0.5% (1.629 ± 0.181) and Saccharomyces cerevisiae at 0.5% (1.459 ± 0.305) minimized the oxidative rancidity in comparation to control diet (2.843 ± 0.109) of Nile tilapia until 12 months of storage.
Estabilidade oxidativa de rações de tilápia contendo Saccharomyces cerevisiae e Spirulina platensis
Keywords: Biomass; Lipid oxidation; Ratio; TBARS